2005
DOI: 10.1016/j.febslet.2004.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin suppresses lipopolysaccharide‐induced cyclooxygenase‐2 expression through the inhibition of nuclear factor for IL‐6 (NF‐IL6) DNA‐binding activity

Abstract: Chrysin is a natural, biologically active compound extracted from many plants, honey and propolis. It possesses potent anti-inflammation, anti-cancer and anti-oxidation properties. The mechanism by which chrysin suppresses COX-2 expression remains poorly understood. In the present report, we investigated the effect of chrysin on the expression of COX-2 in lipopolysaccharide (LPS)-activated Raw 264.7 cells. Chrysin significantly suppressed the LPS-induced COX-2 protein and mRNA expression in a dose-dependent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 39 publications
(46 reference statements)
10
69
0
1
Order By: Relevance
“…We also found that a 4-week intake of resveratrol led to upregulation of hepatic expression of SIRT1 in wild type, but not PPARα knockout mice (submitted). Polyphenolic compounds such as apigenin, chrysin (Liang et al, 1999;Woo et al, 2005), and humulon (Yamamoto et al, 2000) suppress COX-2 expression and activate PPARα and/or γ (Liang et al, 2001;Yajima et al, 2004). These findings suggest that various food-derived components have effects on PPARs and COX-2 that are comparable to those of resveratrol.…”
Section: Citral a Component Of Lemongrass Oilsupporting
confidence: 51%
“…We also found that a 4-week intake of resveratrol led to upregulation of hepatic expression of SIRT1 in wild type, but not PPARα knockout mice (submitted). Polyphenolic compounds such as apigenin, chrysin (Liang et al, 1999;Woo et al, 2005), and humulon (Yamamoto et al, 2000) suppress COX-2 expression and activate PPARα and/or γ (Liang et al, 2001;Yajima et al, 2004). These findings suggest that various food-derived components have effects on PPARs and COX-2 that are comparable to those of resveratrol.…”
Section: Citral a Component Of Lemongrass Oilsupporting
confidence: 51%
“…Caffeic acid also presents immunosuppressive activity, inhibiting the early and late events of T cell activation and the consequent release of cytokines such as IL-2 (Marquez et al, 2004) in an unspecific way of inhibition of ion channels (Nam et al, 2009). Chrysin, a flavonoid isolated from propolis, also seems to suppress the expression of COX-2 by inhibiting a nuclear factor for IL-6 (Woo et al, 2005).…”
Section: Anti-inflammatory and Immunomodulatory Response To Isolated mentioning
confidence: 99%
“…42) Vaticanol C, a resveratrol tetramer, activates PPARα and PPARβ/δ in vitro (5 μM) and in vivo (0.04% of diet for 8 weeks), but has no effect on SIRT1 activation. 32) Polyphenolic compounds such as apigenin, chrysin, 43,44) and humulon 45) ( Fig. 1) suppress COX-2 expression and also activate PPARα and/or γ.…”
Section: Introductionmentioning
confidence: 99%